Analysis of Hypertension in Coastal Areas - Wasiyem, Wasiyem; Purba, Fazri Khoirunnisa; Ayu Maulidia; Larasati, Yulfani; Arzeti, Rintan; Marsha Aulia Putri; Natasya, Khairani (Universitas Ibn Khaldun Bogor, 2025)
Hypertension is a significant risk factor for cardiovascular disease, stroke, renal failure, and blindness, and it is a primary cause of mortality globally. This study aims to analyse the prevalence of hypertension in coastal areas in relation to socio-demographic factors and dietary habits. This study employs a questionnaire approach using a cross-sectional design conducted in December 2024, utilising a sample of 50 participants. This study aims to determine the prevalence of hypertension in the Belawan 1 region and identify contributing variables, including excessive salt intake, insufficient physical exercise, stress, smoking, and genetic predisposition. The following variables contribute to the development of hypertension. Summary: This research seeks to examine the prevalence of hypertension in coastal areas, including socio-demographic factors and dietary habits. The used technique is a questionnaire using a cross-sectional design. “The study findings indicate that many individuals lack comprehension of hypertension and have identified several contributing elements to its development, including a high-salt diet, insufficient physical exercise, stress, smoking, and hereditary predispositions. These results underscore the need of enhancing public knowledge about hypertension and its causative elements, along with the imperative for instruction on healthy lifestyles to avert this condition.